Improving the Ability of Nursing Clinical Supervisors in Implementing Targeted Clinical Learning Models (MPKBT) - Sasmita, Anah; Husni, Ahmad; Z, Desmaniarti; Triantono, Kristoforus; Salasa, Sehabudin (Jurnal Pendidikan Keperawatan Indonesia, 2023)
Clinical learning is a process of interaction between clinical preceptors and students as learners on the practice field. The clinical guidance process is often limited to supervising nursing students during clinical practice without any targets that need to be achieved, even students repeat the same activities every day. This study aims to determine the application of a target-based clinical learning model in improving the quality of preceptors. The study used a quasi-experimental design with a one group time series design on 40 nurses from several hospitals and educational institutions who had not received clinical preceptor training. The sampling technique used quota sampling technique according to the proportion of the number of students who were practicing in their respective institutions, the sample was given an intervention in the form of training using a target-based clinical learning model consisting of theory and practice. The practice was conducted in the laboratory and in the hospital from September to December. Evaluation using a checklist instrument for assessing preceptor competence and data analyzed using the Wilcoxon test using SPSS 25.0.  The result of the study, there was a significant increase in the ability of nurses to provide nursing clinic preceptors between before and after training with a significance value of 0.020, while in the first supervisory assessment significant=0.030, second supervision significant=0.040 and third supervision significant=0.050. The data shows how closely the target-based learning model affects the quality of clinical supervisors' abilities. This is important to be applied to all prospective clinical supervisors before conducting clinical guidance.